EFFECT OF SILICA FUME ON PARTIAL REPLACEMENT OF CEMENT ON HIGH STRENTH CONCRETE - Chakravarthy H.G, Nahushananda; Ali, Farhan Idrees (MATTER: International Journal of Science and Technology, 2015)
The incorporation of silica fume into the normal concrete in the present days to produce the tailor-made high strength concrete the strength of concrete increases with the incorporation of silica fume in partial replacement of cement in a high strength concrete. The main objective of this research work has been made to investigate the compressive strength and flexural strength of concrete by incorporating silica fume. In this present research work 5 (five) different mix of concrete were made incorporating silica fume. These experiments were carried out by replacing cement with different percentages of silica fume at a single constant water-cement ratio keeping other mix design variables constant. The silica fume was replaced by 0%, 5%, 10% and 15% with constant water-cement ratio of 0.40. The silica fume incorporated concrete was tested for 1 day, 7 days, 28 days and 60 days compressive strength and flexural strength. Other fresh concrete properties like compacting factor and slump were also determined for five mixes of concrete to find the workability of the concrete.